Penerapan 3R pada Rumah Tangga Pedesaan: Kajian Determinan Perilaku dan Lingkungan - Sari Arlinda; Mukhlis Mukhlis (Jurnal Sehat Mandiri, 2026)
The increasing volume of household waste in rural areas requires sustainable management based on the principles of Reduce, Reuse, and Recycle (3R). This study aimed to analyze behavioral and structural factors associated with the adoption of 3R practices among housewives in Laban Village, Pesisir Selatan Regency, Indonesia. A cross-sectional study was conducted among 86 randomly selected housewives using a structured questionnaire assessing knowledge, attitudes, infrastructure availability, government support, income level, and the presence of sanitation workers. Data were analyzed using chi-square tests and binary logistic regression. Bivariate analysis showed that knowledge (p = 0.024), attitude (p = 0.046), infrastructure availability (p = 0.007), and government support (p = 0.010) were significantly associated with 3R adoption. Income level and the presence of sanitation workers were not significantly associated. In multivariate analysis, infrastructure availability is dominant factor to 3R adoption in Laban Village (OR = 5,79 dan 95% CI = 1,38–24,21). These findings indicate that improving awareness alone is insufficient without adequate infrastructure and institutional support to promote sustainable household waste management.